Is India's employment guarantee program successfully challenging her historical inequalities? - Kartik Misra (University of Massachusetts, Department of Economics, 2019)
By providing 100 days of guaranteed employment to every rural household, the National Rural Employment Guarantee Act (NREGA) can challenge the hegemony of the landed elite as major employers in the Indian countryside and raise market wages which have long been depressed. This paper shows that the impact of NREGA is conditioned and complicated by historical inequalities in agricultural landownership which have persisted since the colonial period. I find that in the lean season of agriculture, the program is highly successful in raising wages and generating more public employment in districts that were not characterized by historically high levels of socio-economic inequality. In these districts, the increase in public employment crowds-out labor primarily from domestic work, reflected in increased women's participation in the program. However, high inequality in landownership adversely impacts the bargaining power of workers and the enforcement of their entitlements under NREGA. This is most evident when I examine the impact of NREGA on rural wages. I find that in districts where land is concentrated in the hands of relatively few large landowners, private agricultural wages declined despite NREGA, whereas they remain largely unchanged in districts that have more equitable land distribution. These findings are consistent with the hypothesis that NREGA has not become a credible alternative to private employment in regions with high land inequality.
Keywords: O12; I38; J42; J43; P48; 330